X-ray emission spectroscopy as an in situ diagnostic tool for X-ray crystallography of metalloproteins using an X-ray free-electron laser - Fransson, Thomas (Biochemistry, 2018)
Serial femtosecond crystallography (SFX) using the ultrashort X-ray pulses from a X-ray free-electron laser (XFEL) provides a new way of collecting structural data at room temperature that allows for following the reaction in real time after initiation. XFEL experiments are conducted in a shot-by-shot mode as the sample is destroyed and replenished after each X-ray pulse, and therefore, monitoring and controlling the data quality by using in situ diagnostic tools is critical. To study metalloenzymes, we developed the use of simultaneous collection of X-ray diffraction of crystals along with X-ray emission spectroscopy (XES) data that is used as a diagnostic tool for crystallography, by monitoring the chemical state of the metal catalytic center. We have optimized data analysis methods and sample delivery techniques for fast and active feedback to ensure the quality of each batch of samples and the turnover of the catalytic reaction caused by reaction triggering methods. Here, we describe this active in situ feedback system using Photosystem II as an example that catalyzes the oxidation of H2O to O2 at the Mn4CaO5 active site. We used the first moments of the Mn Kβ1,3 emission spectra, which are sensitive to the oxidation state of Mn, as the primary diagnostics. This approach is applicable to different metalloproteins to determine the integrity of samples and follow changes in the chemical states of the reaction that can be initiated by light or activated by substrates and offers a metric for determining the diffraction images that are used for the final data sets.
Gesehen am 16.12.2019